Distinguishing Doors and Floors on All Fours: Landmarks as Tools for Vertical Navigation Learning in Domestic Dogs (Canis familiaris) - Lila Muscosky; Alexandra Horowitz (Animals)
Spatial navigation allows animals to understand their environment position and is crucial to survival. An animal’s primary mode of spatial navigation (horizontal or vertical) is dependent on how they naturally move in space. Observations of the domestic dog (Canis familiaris) have shown that they, like other terrestrial animals, navigate poorly in vertical space. This deficit is visible in their use of multi-story buildings. To date, no research has been conducted to determine if dogs can learn how to navigate in an anthropogenic vertical environment with the help of a landmark. As such, we herein investigate the effect of the addition of a visual or olfactory landmark on dogs’ ability to identify when they are on their home floor. Subject behaviors toward their home door and a contrasting floor door were compared before and after exposure to a landmark outside of their home door. While subjects initially showed no difference in latency to approach an apartment door on their home or a wrong floor, we found a significant difference in latency to approach the doors in the test trials for subjects who approached the doors in every trial. Other findings are equivocal, but this result is consistent with the hypothesis that dogs can learn to navigate in vertical space.